2015
DOI: 10.1002/asia.201500535
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Aerobic Homocoupling of Phenylboronic Acid on Au20: A DFT Study

Abstract: The mechanism of the gold nanocluster-catalyzed aerobic homocoupling of arylboronic acids has been elucidated by means of DFT calculations with Au20(-) as a model cluster for the Au:[poly(N-vinylpyrrolidin-2-one)] catalyst. We found that oxygen affects the adsorption of phenylboronic acid and, by lowering the energy barrier, a water molecule enhances dissociation of the C-B bond, which is probably the rate-determining step. The key role of oxygen is in activating the surface of the gold cluster by generating L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 46 publications
5
29
0
Order By: Relevance
“…As the temperature‐dependent reactivity is often explained by the collision theory, the activation energies of the reaction were calculated from the Arrhenius plot (Figure S7). Apparently, the base‐free homocoupling reaction with the composite (Oxa) (∼31.8 kJ/mol) is easier than that with the composite (Cit) (∼41.4 kJ/mol), which were within the range of reported values …”
Section: Figuresupporting
confidence: 85%
See 1 more Smart Citation
“…As the temperature‐dependent reactivity is often explained by the collision theory, the activation energies of the reaction were calculated from the Arrhenius plot (Figure S7). Apparently, the base‐free homocoupling reaction with the composite (Oxa) (∼31.8 kJ/mol) is easier than that with the composite (Cit) (∼41.4 kJ/mol), which were within the range of reported values …”
Section: Figuresupporting
confidence: 85%
“…The coupling of hydrophilic 4‐hydroxyphenylboronic acid led to a relatively low yield, which was possibly caused by the deprotonation of the slightly acidic alcohol in the phenol group. This process might compete against the formation of 4‐hydroxyphenyl‐B(OH) 3 − species in the base‐free coupling reactions . Extending the reaction time (e. g., 8 h) appreciably increased the yields of all products to moderately overcome the steric and miscibility barriers under the same reaction conditions.…”
Section: Figurementioning
confidence: 99%
“…A twenty‐atom gold cluster (Au 20 ) was selected based on our previous works. The Au 20 − model cluster has been used successfully to simulate methanol oxidation on a Au:PVP system, as well as for modeling homocoupling reactions of chloroarenes and phenylboronic acid on the same colloidal Au NC catalyst. The selection of this cluster was based on the observation that it has a significantly lower electron affinity than other gold clusters up to 58 atoms .…”
Section: Computational Detailsmentioning
confidence: 99%
“…The M06 functional has been demonstrated to be a useful functional for applications in transition‐metal‐containing systems . In particular, we have recently shown that DFT calculations with the M06 functional is suitable for the study of chemical reactions on Au NCs . Benchmark calculations using the left‐eigenstate complete renormalized‐coupled cluster method with singles, doubles, and noniterative triples (CR‐CC(2,3)) for the reaction on Au NCs showed that M06 and B3LYP work well for the activation energy barrier, whereas B3LYP overestimates the reaction energy .…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation